1998
DOI: 10.3181/00379727-217-44243
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of Genistein on Bone Tissue in the Ovariectomized, Lactating Rat Model

Abstract: The ovariectomized (OVX), lactating rat model has been used to investigate the skeletal effects of the plant estrogen, genistein, over a 14-day period. The OVX, lactating rat on a low-calcium diet loses slightly more than 50% of its bone mineral mass during the first 2 weeks of lactation, and we have demonstrated that estrogen treatment can significantly reduce the loss of femoral mass (ash weight). Following OVX, the rats were assigned to treatment or control groups (both placebo and positive control with est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
2
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(90 citation statements)
references
References 9 publications
7
77
2
4
Order By: Relevance
“…The ovariectomy (OVX) rat is the most commonly used animal model for evaluating the mechanisms underlying postmenopausal osteoporosis and therapeutic strategies for treating this disease (6)(7)(8)(9). However, compared with rats, mice may be a more effective model as they have a more easily manipulated genome and lower drug doses are required for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The ovariectomy (OVX) rat is the most commonly used animal model for evaluating the mechanisms underlying postmenopausal osteoporosis and therapeutic strategies for treating this disease (6)(7)(8)(9). However, compared with rats, mice may be a more effective model as they have a more easily manipulated genome and lower drug doses are required for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16) There are several reports that genistein inhibits osteoclastic activity and can reduce bone loss in ovariectomized rats. 9,[17][18][19] Moreover, it has been found that genistein has an anabolic effect on bone formation and mineralization by cultured bone cells. 15,20) Genistein also inhibits bone resorption in femoral metaphyseal tissues obtained from elderly rats in vitro.…”
mentioning
confidence: 99%
“…All three of the studies incorporated the phyto-oestrogencontaining preparation into the diet; however, the doses used are difficult to compare. The phytooestrogen content was not determined in the soy protein isolate in the Arjmandi et al 46 study, and the phyto-oestrogen preparation used by Anderson et al 47 was only partially purified.…”
Section: Rodent Studiesmentioning
confidence: 99%
“…Studies from three different laboratories using OVX rats have shown that treatment with the isoflavones present in soy, either unpurified 46 , partially purified 47 or purified 48 (as genistein) exerted significant improvement in bone mass and approximately the same per cent retention, which may approach the gain from treatment with replacement doses of oestradiol (Fig. 6).…”
Section: Rodent Studiesmentioning
confidence: 99%
See 1 more Smart Citation